Pianismo de concerto no Rio de Janeiro do século xix - Faria, Paulo Rogério Campos de (1996)
The object of our study is the introduction, in the city of Rio de Janeiro, of a new concept of piano playing, during the nineteenth century, what we call concert-pianism. At that time. it meant a new approach conceming piano playing; namely, the new focus on the solists, the intemational virtuosi that began giving concerts in the city, very much in the tradition of romanticism : the world touring heroe-artist, the genius, and so on. The fact bears,connections with the society structural transformations, which the country was going through. This approach had a counterpart in what we call salon-pianism, which means basically private music in homes, salons or even small events, to which ball music, singing and instrumental performance of technically non-complex music is related. We try to work out, in the study of the phenomenon, two complementary approaches: one interpreting analysis, in a dialetical basis, as to connect it to the wider range of social history. On the other hand, giving it a treatment of a communication phenomenon, we make an attempt to identify the constituting elements of the aesthetic message, and at last, the way it relates to the social structure.